A critical introduction to coaching & mentoring debates, dialogues & discourses - Gray, David E. (David Edward) 1952-; Garvey, Bob; Lane, David A. 1947- (SAGE, 2016)
This is the definitive introduction to coaching and mentoring, written by an experienced and multidisciplinary team. Taking you all the way through from the emerging theory to informed practice, the book covers: " Skills, purposes and outcomes of coaching and mentoring processes " The many settings in which they take place - public, private and voluntary " Coaching and mentoring's evidence base and how it is assessed " The professionalization of coaching and mentoring and a move towards integration. Supported by a wide range of case studies, activities, further questions and topics for discussion, this book is a comprehensive but accessible introduction. The authors take a critical approach and go beyond the basics, to support your development as a critically reflective practitioner. It is essential reading for those studying coaching and mentoring, and professionals looking to integrate coaching and mentoring into their organizations.